ASTHENIC DISORDERS IN ELDERLY PATIENTS WITH ARTERIAL HYPERTENSION: MANAGEMENT POTENTIAL OF MELDONIUM - M. E. Statsenko; S. V. Nedogoda; S. V. Turkina; I. A. Tyshchenko; L. V. Poletaeva; V. V. Tsoma; A. A. Ledyaeva; E. V. Chumachok (Столичная издательская компания, 2015)
Aim. To assess the effect of meldonium (in combination with antihypertensive therapy) on the severity of asthenic syndrome (AS) in elderly patients with arterial hypertension (HT).Material and methods. Patients (n=180, >65 years old) with HT (grade 1-2) and secondary somatogenic AS (assessed by the MFI-20 scale). The patients were randomized into 3 groups according to the scheme of treatment. Group 1 - intermittent treatment with meldonium (500 mg once daily for 3 months followed by a break 3 months; 2 courses). Group 2 - continuous treatment with meldonium (500 mg once daily for 12 months). Group 3 - control (receive only antihypertensive drugs). Evaluation of AS was assessed by MFI-20 scales at baseline and at week 52 of treatment.Results. AS signs attenuation was found in groups 1 and2. In group1 a number of patients with general asthenia decreased on 70.5% (p<0.05), with physical asthenia - on 47.7% (p<0.05), with reduced activity - on 33.3%, reduced motivation - on 25%. In group2 a number of patients with general asthenia decreased on 60% (p<0.05), physical asthenia - on 39.7%, reduced activity - on 79.9% (p<0.05), reduced motivation - on 12.2%, mental asthenia - on 77.7% (p<0.05). In group 3 no significant changes in these parameters were found. Moreover a number of patients with mental asthenia increased on 45.4% (p<0.05).Conclusion. Meldonium included into antihypertensive therapy can reduce the symptoms of secondary somatogenic AS. More pronounced antiasthenic effect can be achieved with meldonium taking regime 500 mg daily continuously for 52 weeks.